Youtube as a Medium for Distributing the Philosophy of Science: The Peak of Goodness is in Love - Elya Afifah Yusuf; Kun Wazis; Siti Raudhatul Jannah; Dwi Ayu Wulandari; Indah Pramitha Sari (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Through his YouTube account, the uploaded content is very interesting to listen to and has an implicit message in the YouTube channel "Cahaya Cinta Untuk Indonesia". which aims to be studied to understand various aspects of life. In this content, Habib Husein Ja'far collaborated with Dr. Fahhrudin Faiz entitled "The Peak of Goodness is in Love", where they both discuss philosophical studies, namely where humans are not perfect creatures, there are always shortcomings, always not reaching the most correct point, especially in studying philosophy, their egos must rise because they feel they can think philosophically, the key is knowledge and love without both, life will be chaotic, you could say people are illogical and many more. In this study, the researcher used a qualitative research approach with a descriptive research type with technical transcript analysis. The purpose of this study is toEffectiveness Evaluation Assessing the effectiveness of communication media (YouTube) in disseminating philosophical thoughts, Impact Identification Identifying the positive or negative impact of content on audience behavior and thinking.